2010
DOI: 10.1186/1471-2253-10-7
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison between three types of irrigating fluids during transurethral resection in benign prostatic hyperplasia

Abstract: Background: Central nervous system changes, circulatory and electrolyte imbalances are the main complications of endoscopic transurethral resection of the prostate (TURP) which is known as transurethral resection (TUR) syndrome, which occurs as result of excessive absorption of irrigating fluid. We compare glycine 1.5% versus glucose 5% and normal saline 0.9% as irrigating solutions during TURP in patients with moderate to severe bladder outlet obstruction due to benign prostatic hyperplasia (BPH). Methods:Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 16 publications
1
42
1
Order By: Relevance
“…The δ5.5-9.0 region (dashed box) was magnified 10 times relative to the δ0.5-5.5 region for clarity. The samples K 1-15 , K 1-16 , K 2-8 , K [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] , and C 8 were removed to achieve a better quality of spectrum and a better suppression effect of the water peak. The data were subsequently analyzed using multivariate statistics (PCA and OPLS-DA).…”
Section: H-nmr Spectroscopy Of Plasma Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The δ5.5-9.0 region (dashed box) was magnified 10 times relative to the δ0.5-5.5 region for clarity. The samples K 1-15 , K 1-16 , K 2-8 , K [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] , and C 8 were removed to achieve a better quality of spectrum and a better suppression effect of the water peak. The data were subsequently analyzed using multivariate statistics (PCA and OPLS-DA).…”
Section: H-nmr Spectroscopy Of Plasma Samplesmentioning
confidence: 99%
“…In general, ketosis is closely related to negative energy balance (NEB), poor appetite, and high milk production during early lactation, which may contribute to inadequate energy intakes [2]. There are two types of ketosis: clinical ketosis and subclinical ketosis, based on the clinical symptoms, e.g., anorexia, depression, decreased milk production, constipation, drowsiness or nervousness [3], and plasma 3-hydroxybutyrate acid levels (BHBA, >1.20 mmol/L) [4]. However, Holtenius et al [5] reported that ketosis in dairy cattle is divided into types I and II based on the disease characteristics and clinical features.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, troponin levels also rose equally in patients who received glycine or glucose, but only serum glycine correlated with ischaemic changes on the ECG [32]. Yousef et al [33] reported that 6 out of 120 patients developed ischaemic changes on the ECG and that 3 showed elevated serum troponin levels after the surgery; this occurred only with glycine irrigation.…”
Section: Special Problems With Glycinementioning
confidence: 99%
“…Yousef et al [33] compared symptoms in 360 patients following irrigation with glycine 1.5%, glucose 5% and isotonic saline. The resection weights were unusually large (average 90 g).…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation